Effect of incorporation of graphene oxide and graphene nanoplatelets on mechanical and gas permeability properties of poly(lactic acid) films - Artur M. Pinto (2013)
Nanocomposite thin films of poly(lactic acid) (PLA) were produced incorporating small amounts (0.2 to 1 wt%) of graphene oxide (GO) and graphene nanoplatelets (GNP). The films were prepared by solvent-casting. Mechanical properties were evaluated for plasticized (by residual solvent) and unplasticized films. Plasticized nanocomposite films presented yield strength and Young's modulus about 100% higher than those of pristine PLA. For unplasticized films improvements in tensile strength and Young's modulus were about 15 and 85%, respectively. For both film types, a maximum in mechanical performance was identified for about 0.4 wt% loadings of the two filler materials tested. Permeabilities towards oxygen and nitrogen decreased, respectively, three-and fourfold in films loaded with both GO or GNP. The glass transition temperature showed maximum increases, in relation to unloaded PLA films, of 5 degrees C for 0.4 wt% GO and 7 degrees C for 0.4 wt% GNP, coinciding with the observed maxima in mechanical properties. (C) 2012 Society of Chemical Industry